2009
DOI: 10.1109/tit.2009.2023727
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Capacity of the Compound Channel

Abstract: In this work we find the capacity of a compound finite-state channel with time-invariant deterministic feedback. The model we consider involves the use of fixed length block codes. Our achievability result includes a proof of the existence of a universal decoder for the family of finite-state channels with feedback. As a consequence of our capacity result, we show that feedback does not increase the capacity of the compound Gilbert-Elliot channel. Additionally, we show that for a stationary and uniformly ergod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…By Corollary 1, feedback does not increase the capacity of the Gilbert-Elliot channel and it should be noted that this result is a special case of [11] and [13]. Since |X | = 2, the feedback capacity of the Gilbert-Elliot channel can be found as…”
Section: A Gilbert-elliot Channel (Eg [3])mentioning
confidence: 80%
See 1 more Smart Citation
“…By Corollary 1, feedback does not increase the capacity of the Gilbert-Elliot channel and it should be noted that this result is a special case of [11] and [13]. Since |X | = 2, the feedback capacity of the Gilbert-Elliot channel can be found as…”
Section: A Gilbert-elliot Channel (Eg [3])mentioning
confidence: 80%
“…It is also shown that for any channel with memory satisfying the symmetry conditions defined in [12], feedback does not increase its capacity. Recently, it has been shown that feedback does not increase the capacity of the compound Gilbert-Elliot channel [13], which is a family of FSM channels. In a related work, the capacity of finite-state indecomposable channels with side information at the transmitter is investigated [14].…”
mentioning
confidence: 99%
“…We denote the probability mass function (pmf) of causally conditioned on , for some integer , as which is defined as Directed information has been widely used in the characterization of capacity of point-to-point channels [8], [18]- [22], compound channels [23], network capacity [24], rate distortion [25], [26], and broadcast channel [27]. Directed information can also be expressed in terms of causal conditioning as (37) where denotes expectation.…”
Section: Alternative Proofmentioning
confidence: 99%
“…Proof: It suffices to prove the claim assuming as in (11) and that is the -dimensional vector with components (17) For such and , we have from (16)…”
Section: Proposition 1: Let and Be Partitions Inmentioning
confidence: 99%
“…The upper bound in (1) is tight for certain classes of ergodic channels, such as general nonanticipatory channels satisfying certain regularity conditions [3], channels with finite input memory and ergodic noise [4], and indecomposable finite-state channels [5], paving the road to a computable characterization of feedback capacity (see [6]- [8] for examples). Directed information and its variants also characterize (via multiletter expressions) the capacity for two-way channels [2], multiple access channels with feedback [2], [9], broadcast channels with feedback [10], and compound channels with feedback [11], as well as the rate-distortion function with feedforward [12], [13]. In another context, directed information captures the difference in growth rates of wealth in horse race gambling due to causal side information [14].…”
Section: Introductionmentioning
confidence: 99%